Regionalism and diffusion revisited: From final design towards stages of decision-making. Issue 4 (14th January 2016) - Duina, Francesco; Lenz, Tobias
Abstract: An emerging research programme on diffusion across regional international organisations (RIOs) proposes that decisions taken in one RIO affect decision-making in other RIOs. This work has provided a welcome corrective to endogenously-focused accounts of RIOs. Nevertheless, by focusing on the final design of policies and institutional arrangements, it has been conceptually overly narrow. This has led to a truncated understanding of diffusion's impact and to an unjustified view of convergence as its primary outcome. Drawing on public policy and sociological research, we offer a conceptual framework that seeks to remedy these weaknesses by disaggregating the decision-making process on the 'receiving' side. We suggest that policies and institutional arrangements in RIOs result from three decision-making stages: problematisation (identification of something as a political problem), framing (categorisation of the problem and possible solutions), and scripting (design of final solutions). Diffusion can affect any combination of these stages. Consequently, its effects are more varied and potentially extensive than is currently recognised, and convergence and persistent variation in scripting are both possible outcomes. We illustrate our framework by re-evaluating research on dispute settlement institutions in the EEC, NAFTA, and SADC. We conclude by discussing its theoretical implications and the conditions that likely promote diffusion.